3x(5y+38)(8x+26)=

Simple and best practice solution for 3x(5y+38)(8x+26)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x(5y+38)(8x+26)= equation:


Simplifying
3x(5y + 38)(8x + 26) = 0

Reorder the terms:
3x(38 + 5y)(8x + 26) = 0

Reorder the terms:
3x(38 + 5y)(26 + 8x) = 0

Multiply (38 + 5y) * (26 + 8x)
3x(38(26 + 8x) + 5y * (26 + 8x)) = 0
3x((26 * 38 + 8x * 38) + 5y * (26 + 8x)) = 0
3x((988 + 304x) + 5y * (26 + 8x)) = 0
3x(988 + 304x + (26 * 5y + 8x * 5y)) = 0

Reorder the terms:
3x(988 + 304x + (40xy + 130y)) = 0
3x(988 + 304x + (40xy + 130y)) = 0
3x(988 + 304x + 40xy + 130y) = 0
(988 * 3x + 304x * 3x + 40xy * 3x + 130y * 3x) = 0

Reorder the terms:
(2964x + 390xy + 912x2 + 120x2y) = 0
(2964x + 390xy + 912x2 + 120x2y) = 0

Solving
2964x + 390xy + 912x2 + 120x2y = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '6x'.
6x(494 + 65y + 152x + 20xy) = 0

Ignore the factor 6.

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(494 + 65y + 152x + 20xy)' equal to zero and attempt to solve: Simplifying 494 + 65y + 152x + 20xy = 0 Reorder the terms: 494 + 152x + 20xy + 65y = 0 Solving 494 + 152x + 20xy + 65y = 0 Move all terms containing x to the left, all other terms to the right. Add '-494' to each side of the equation. 494 + 152x + 20xy + -494 + 65y = 0 + -494 Reorder the terms: 494 + -494 + 152x + 20xy + 65y = 0 + -494 Combine like terms: 494 + -494 = 0 0 + 152x + 20xy + 65y = 0 + -494 152x + 20xy + 65y = 0 + -494 Combine like terms: 0 + -494 = -494 152x + 20xy + 65y = -494 Add '-65y' to each side of the equation. 152x + 20xy + 65y + -65y = -494 + -65y Combine like terms: 65y + -65y = 0 152x + 20xy + 0 = -494 + -65y 152x + 20xy = -494 + -65y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

x = {0}

See similar equations:

| (6-16)/(2-7) | | 6-16/2-7 | | 3(2+x)=7 | | A+B=60B | | 40=-5n/8 | | p=(g-9)180forg | | 5/x=481 | | x/7=3912 | | 3x^2+x=240 | | -(5/3)x+(2/3)=-11 | | (5m-3n)(4m-2n)=0 | | 3cosx=1 | | y=(x-1)2 | | 27=-3c-3(6-2c) | | y-2=2/3 | | 4+-8y=1.75+y | | 4.4y-4.2=8.1y-1.24 | | 12d+5=5d+12 | | x^2+5x-100= | | (x+a)(x+b)=(x+a)x+(x+a)b | | 7y-4y=63-6y | | 4z(15-7z)-5(2-7)= | | 6(x-2)=3x-8+3x | | 3(2x+1)+4(x-2)=3x+1 | | 9(x-9)=-33.3 | | 4x^2+4x=12 | | 10-x+6x+5=-10x-25 | | 8(a+9)=142.4 | | 33.8=4c-3 | | 9e-5=80.5 | | 3(7x-5)+3(10-4x)-4(2x+3)=-2 | | x^2+(-10.7)x+(-95.7)=0 |

Equations solver categories